Artificial intelligence and soft computing. 16th International Conference, ICAISC 2017, Zakopane, Poland, June 11-15, 2017, Proceedings /: 16th International Conference, ICAISC 2017, Zakopane, Poland, June 11-15, 2017, Proceedings. Part II : (2017) - Unknown
No abstract available